2023
DOI: 10.1111/bjet.13316
|View full text |Cite
|
Sign up to set email alerts
|

Students' prior knowledge moderates the effects of group motivation compositions on learning from video lectures

Abstract: The present study examined whether students' prior knowledge moderated the effects of their motivation compositions on learning performance (ie, retention and transfer) and interaction (ie, interpersonal brain synchronization (IBS) and behavioural pattern) in learning from video lectures. The results confirmed the benefits of the composition of two high motivation students on their knowledge transfer. The results also showed that students' prior knowledge had a moderating effect on interaction. For low prior k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Our focus was on the MNS, rTPJ, dlPFC, and aPFC regions, as previous studies have reported activations in these regions related to coviewing video lectures and social interaction (Azhari et al, 2021;Pi et al, 2023). In the present study, the MNS region covered the IPL and SMG.…”
Section: Fnirs Data Collectionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our focus was on the MNS, rTPJ, dlPFC, and aPFC regions, as previous studies have reported activations in these regions related to coviewing video lectures and social interaction (Azhari et al, 2021;Pi et al, 2023). In the present study, the MNS region covered the IPL and SMG.…”
Section: Fnirs Data Collectionmentioning
confidence: 82%
“…Therefore, we adopted a hyperscanning based on functional near-infrared spectroscopy (fNIRS) to record cortical hemodynamic activity from two brains simultaneously during co-viewing video lectures and compute the degree of similarity or reciprocal influence of one brain signal over the other (i.e., interpersonal brain synchronization, IBS; Azhari et al, 2020Azhari et al, , 2021. IBS can act as a direct and neural indicator of the peer interaction level during the co-viewing of video lectures (Pi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations